2012
DOI: 10.1001/archinternmed.2011.625
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use and Risk of Diabetes Mellitus in Postmenopausal Women in the Women's Health Initiative

Abstract: Statin medication use in postmenopausal women is associated with an increased risk for DM. This may be a medication class effect. Further study by statin type and dose may reveal varying risk levels for new-onset DM in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
255
2
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(279 citation statements)
references
References 45 publications
14
255
2
8
Order By: Relevance
“…47,224,226,227 Prior to these reports from randomized trials, adverse associations had not been reported between statin therapy and diabetes incidence in observational studies, although several reports of such associations have been published subsequently. 228,229 Recently, it has been found that genetic variants that reduce the activity of HMGCoA reductase (which is analogous to inhibiting this enzyme with a statin) are associated with increased incidence of diabetes. 230 On the other hand, individuals with familial hypercholesterolaemia -in whom the numbers and function of LDL-receptors on cell surfaces are reduced (by contrast with the increase in receptors produced by statins) -had been diagnosed with diabetes less frequently than their unaffected relatives.…”
Section: Increases In Rates Of Diabetes Mellitusmentioning
confidence: 99%
“…47,224,226,227 Prior to these reports from randomized trials, adverse associations had not been reported between statin therapy and diabetes incidence in observational studies, although several reports of such associations have been published subsequently. 228,229 Recently, it has been found that genetic variants that reduce the activity of HMGCoA reductase (which is analogous to inhibiting this enzyme with a statin) are associated with increased incidence of diabetes. 230 On the other hand, individuals with familial hypercholesterolaemia -in whom the numbers and function of LDL-receptors on cell surfaces are reduced (by contrast with the increase in receptors produced by statins) -had been diagnosed with diabetes less frequently than their unaffected relatives.…”
Section: Increases In Rates Of Diabetes Mellitusmentioning
confidence: 99%
“…61 In a secondary analysis of the Women's Health Initiative data, statin use was associated with an increased risk of diabetes (adjusted hazard ratio [HR] 1.48; 95 % CI 1.38-1.59). 62 Other observational studies have noted higher adjusted risk of incident diabetes among statin users versus nonusers. ranging from 2.8 to 4.7.…”
Section: Discussionmentioning
confidence: 97%
“…However, very few studies have compared the diabetogenic effects of statins across different races. Recently, a sub-analysis of observational data from the Women's Health Initiative (WHI) suggested that, compared to statin non-users, statintreated post-menopausal women (N ¼ 3922) from Asia and the Pacific Islands had a non-significant trend towards a higher risk of developing T2D (HR 1.78; 95% CI 1.32e2.40) than their Caucasian (HR 1.49; 1.38e1.62) and African American counterparts (HR 1.18; 0.96e1.45) [106]. These results must be cautiously interpreted given the observational nature of the data.…”
Section: Is the Diabetogenicity Of Statins Consistent Across All Patimentioning
confidence: 99%